Pengembangan Media Evaluasi Hearsmon Berbasis SEL (Social Emotional Learning) dalam Pembelajaran IPA Materi Sistem Pendengaran Bagi Siswa SD - Kismiati, Dyah Aniza (Fakultas Bahasa dan Sains, Universitas Wijaya Kusuma Surabaya, 2020)
This study aims to develop a media evaluation based on monopoly games combined with the values of Social Emotional Learning (SEL) on hearing system material for Grade IV Primary School students. This type of research is a Research and Development (RnD) with ADDIE design (Analysis, Design, Develop, Implement, and Evaluate). The stages carried out for this research are limited to the Development stage. The results of this study are in the form of a monopoly evaluation media, hereinafter referred to as Hearsmon, which contains test instruments related to the hearing system material for grade IV students. The values of Social Emotional Learning (SEL) developed through this media include personal dimensions (self-awareness, self-efficacy, self-management) and social dimensions (respect for others).